Experimental Studies of the Stress-Strain State of Rigid Sewer Pipes - Abdumuminov E. (Scientific Trends, 2024)
The purpose of the article is to study the stress-strain state of rigid underground pipes under various laying and loading conditions. Here attention is paid to testing pipes using a two-force scheme in underground conditions.
Keywords: Stress, strain, pipe, strength, soil.